Pengaruh Strategi Pembelajaran Snowball Throwing Terhadap Hasil Belajar PPKn Peserta Didik Kelas VIII - Reysti Ani Safitri; Hermi Yanzi; Nurhayati Nurhayati (Jurnal Kultur Demokrasi, 2020)
The purpose of this study was to determine a significant effect on the use of snowball throwing learning strategies on learning outcomes of the eighth grade PPKn at SMP Negeri 2 Adiluwih. The research method used was quasi-experimental with a quantitative. Data collection techniques used were test questions as the main technique while interviews, observation and documentation as supporting techniques. The question technique is calculated using the product moment formula, alpha cronbach, simple linear regression, percentage. Based on the results of the study showed that there was a difference in the improvement of the learning outcomes of PPKn eighth grade students at Adiluwih State Junior High School 2 using snowball throwing learning strategies and students using conventional learning. The difference in learning outcomes is indicated by the average value using the snowball throwing learning strategy 83.78 while those using conventional learning 76.02. From the posttest, it can be seen that the class that uses the snowball throwing learning strategy has a higher valueTujuan penelitian ini adalah untuk mengetahui pengaruh yang signifikan pada penggunaan strategi pebelajaran snowball throwing terhadap hasil belajar PPKn kelas VIII di SMP Negeri 2 Adiluwih. Metode penelitian yang digunakan adalah kuasi eksperimen dengan pendekatan kuantitatif. Teknik pengumpulan data yang digunakan yaitu tes soal pretest, posttest, wawancara, observasi dan dokumentasi. Teknik analisis dihitung dengan product moment, alpha cronbach, regesi linier sederhana, presentase. Berdasarkan hasil penelitian menunjukkan bahwa terdapat perbedaan peningkatan kemampuan hasil belajar PPKn peserta didik kelas VIII SMP Negeri 2 Adiluwih yang menggunakan strategi pembelajaran snowball throwing dengan peserta didik yang menggunakan pembelajaran konvesional. Perbedaan hasil belajar di tunjukan oleh nilai posttest yang menggunakan strategi pembelajaran snowball throwing 83,78 sedangkan yang menggunakan pembelajaran konvesional 76,02. Dari nilai posttest tersebut terlihat bahwa kelas yang menggunakan strategi pembelajaran snowball throwing lebih tinggi nilainya.Kata kunci : strategi, snowball throwing, hasil belajar